Characterization of Fiber Bragg Grating (FBG) for Weight Measurement System - Rosyida, Ainur; Fatimah, Nur Hidayah; Nugroho, Kacuk Cikal; Rahmat, Rahmat; Ismail, Zuhdi; Muhammad, Muhammad; Hanto, Dwi (Applied mechanics and materials, 2023)
Currently, FBG sensor has been developed in many applications due to its wavelength is sensitive to pressure change. This study aims to analyze the FBG wavelength shifting due to an applied load. In this research, the FBG was placed transversely right in the middle of the specimen that was made by using silicon rubber with thicknesses of 7 mm and 14 mm. The FBG wavelength in the two specimens was investigated by an interrogator when the load is put on to the specimens in three variations: without load, 5 kg, and 10 kg. The result show that the shift of FBG wavelength in specimen with the same thickness is proportional to load increasing. Furthermore, the test specimen with a thickness of 7 mm is more sensitive than 14 mm. Accordingly, the specimen with a thickness of 7 mm is a good option to be used as a weight measurement system.